PENELITIAN PROSPEK PENGEMBANGAN USAHA PENGOLAHAN GULA AREN (Arenga pinnata merr.) PADA RUMAH PRODUKSI HENAHUAFIZ DI DESA PESAYANGAN BARAT KECAMATAN MARTAPURA KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Baparki, Ahmad; Budiwati, Nina (Chlorophyl, 2025)
The primary objective of the research on the prospects for developing the Palm Sugar processing business at the Henahuafiz Production House in Pesayangan Barat Village, Martapura District, Banjar Regency, South Kalimantan Province, is to technically determine the palm sugar production process, analyze the magnitude of costs, revenues, business income, and identify and solve existing problems. Furthermore, it aims to determine the development prospects so that it can serve as a case study for the community interested in this field. The resulting products have evolved from ordinary palm sugar to various variants, such as granular palm sugar (large and mini), ant-sugar (palm sugar powder), liquid palm sugar, and ginger palm sugar. The average production during September 2025, or 3-4 production cycles, yielded 489 kg of Large Granular Palm Sugar with a price of Rp 23,000/kg, resulting in a total revenue (TR) of Rp 11,247,000 (eleven million two hundred forty-seven thousand rupiah) and 75 kg of Small Granular Palm Sugar with a price of Rp 24,000/kg, resulting in a total revenue (TR) of Rp 1,800,000 (one million eight hundred thousand rupiah). Thus, the total revenue for September 2025 was Rp 13,047,000 (thirteen million forty-seven thousand rupiah), with the total income from this business amounting to Rp 3,229,911 (three million two hundred twenty-nine thousand nine hundred eleven rupiah) for the month of September 2025.